Enhancing user engagement with ergonomic e-waste recycling bins in retail environments - Hasbullah, Nornajihah Nadia; Muthusamy, Geetha; Naseri, Roszi Naszariah Nasni; Yahya, Wan Kalthom (Faculty of Art and Design, 2025)
Electronic waste (e-waste) disposal remains a significant environmental challenge in Malaysia, particularly within urban retail environments. This study aims to understand the factors that influence consumers’ intentions to recycle e-waste, focusing on Generation Y. Guided by the Theory of Planned Behaviour (TPB), the research examines how attitudes, perceived behavioural control, subjective norms, influencer credibility, and ergonomic design impact recycling intentions. An online survey will be collected from 200 respondents via purposive sampling, and Partial Least Squares Structural Equation Modelling (PLS-SEM) will be used for analysis. The findings are expected to show that positive attitudes, perceived ease of recycling, strong social norms, and credible influencer attributes significantly increase the intention to recycle e-waste. Ergonomic design features are also anticipated to enhance perceived behavioural control. The study concludes that promoting awareness, improving design, and leveraging social influence can effectively increase e-waste recycling participation. The contribution of this research lies in providing actionable insights for retailers and policymakers to develop effective strategies that boost recycling efforts and support sustainable waste management in Malaysia.